FREE RADICAL MEDIATED DISEASES AND THEIR PREVENTION : AN AYURVEDIC PERSPECTIVE - Chutia, *Bijita; Basumatary, Khagen (International Journal of Ayurveda and Pharma Research, 2016)
Free radical production occurs continuously in all cells as part of normal cellular function. However, excess free radical production originating from endogenous or exogenous sources might play a role in many diseases. Antioxidants prevent free radical induced tissue damage by preventing the formation of radicals, scavenging them, or by promoting their decomposition. The disease preventive and health promotive approach of 'Ayurveda', which takes into consideration the whole body, mind and spirit while dealing with the maintenance of health, promotion of health and treating ailments is holistic and finds increasing acceptability in many regions of the world. Ancient Ayurvedic physicians had developed certain dietary and therapeutic measures to arrest/delay ageing and rejuvenating whole functional dynamics of the body system. This revitalization and rejuvenation is known as the 'Rasayan chikitsa' (rejuvenation therapy). Rasayana is intended in classical Ayurveda as an effective tool to synthesize the excellent quality of Dhatu that entails the prevention and alleviation of senility and diseases. Experimental studies done on various Rasayana drugs prove that they have immune stimulant, antioxidant, adaptogenic and anti-stress properties. Rasayana drugs consist of the substances which are rich in Vitamin C, Vitamin E, Beta carotene, riboflavin. So these substances are capable of counteracting the damaging effect of oxidation by working as anti-oxidants & prevent aging process. Over about 100 disorders like rheumatoid arthritis, hemorrhagic shock, CVS disorders, cystic fibrosis, metabolic disorders, neurodegenerative diseases, gastrointestinal ulcerogenesis and AIDS have been reported as reactive oxygen species mediated. In this review, the role of free radicals in these diseases has been briefly reviewed. 'Rasayana' plants with potent antioxidant activity have been reviewed for their traditional uses, and mechanism of antioxidant action.